ANALISIS EFEKTIVITAS PENGGUNAAN ANGGARAN PENDAPATAN DAN BELANJA DESA STUDI KASUS LEMBANG BARUPPU’ KECAMATAN BENTENG BATU KABUPATEN TORAJA UTARA - Jelvita; Helba Rundupadang; Dina Ramba’ (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the effectiveness level of the Lembang Income and Expenditure Budget (APBL) utilization in Lembang Baruppu’, Benteng Batu District, North Toraja Regency, for the 2021–2024 period, and to identify the inhibiting factors that affect budget absorption.  The research method employed is descriptive quantitative. The data used consists of secondary data sourced from the Realization Reports of the Income and Expenditure Budget of Lembang Baruppu’ from 2021 to 2024. The data analysis technique was carried out by calculating the financial effectiveness ratio based on the comparison between the budget realization and the predetermined targets, referring to the standards of Kepmendagri No. 600.900-327 of 1996.  The results of the study indicate that the revenue effectiveness level in Lembang Baruppu’ for the 2021–2024 period falls into the highly effective and effective categories, with the average percentage of revenue realization closely reaching the budget targets each year. However, budget expenditure realization shows a fluctuating and declining trend until 2024. There is a budget variance in the form of Unspent Village Funds (SiLPA) caused by suboptimal expenditure absorption. The primary inhibiting factors in budget absorption include the limited competence and human resource quality of lembang officials in financial administration, technical constraints in adjusting work programs, and geographical challenges in executing physical development activities in the field.